Evaluation of pre-service teachers’ digital competence in Limpopo province, South Africa - Jere, Samuel; Mpeta, Mamotena (Penerbit Universiti Kebangsaan Malaysia, 2024)
Digital technology can potentially improve the quality of education in rural communities by creating conducive conditions for collaboration among learners, providing interactive learning tools and offering opportunities for personalised learning experiences. The pre-service teachers are a critical human resource in improving the quality of education. Therefore, this study investigated the perceptions of pre-service teachers’ technical, pedagogical, attitudinal and ethical digital competence and their readiness to use digital technologies to enhance their teaching practices in Limpopo Province in South Africa. The theoretical framework that guided the study was the Pedagogical, Ethical, Attitudinal and Technical model (PEAT). This descriptive study used a quantitative approach by employing a cross-sectional survey design. A conveniently selected sample of 123 pre-service teachers participated in the study. The research instrument used to collect data was a Questionnaire of Pre-service Teachers’ Digital Competence. The quantitative data collected were analysed using descriptive statistics. The study's findings were that preservice teachers had positive attitudes towards digital technologies, perceived themselves as having high technical digital competence and perceived ICT use in school as contributing positively to learning. They had lower perceptions regarding their competences in using specific digital technologies in teaching and their knowledge of ethical issues. They had the lowest perceptions in the university's role in preparing them for integrating digital technologies into teaching. These findings underscore the necessity of teacher educators to explore new strategies to enhance student teachers' digital competences.